The costs of antimerger lawsuits - Wier, Peggy (Journal of Financial Economics, 1983)
This paper presents tests of the hypothesis that the relief imposed in antimerger cases is costly for defendant firms' stockholders. Previous research on this subject suggests that defendants' case-related losses are due entirely to legal expenses and the disruption of productive activity. In this paper it is shown that two out of five portfolios of defendant firms earn abnormal losses when final decisions in antimerger cases are announced. These losses are consistent with the imposition of costly constraints on some defendants by government antitrust enforcers. The tests also show that when acquisitions are canceled following antimerger complaints, the losses to the target firms are substantial and completely offset the gains generated when the acquisitions are proposed.